Птицы садов и виноградников Закарпатья - Талпош, В.С. (Вестник зоологии, 1976)
Calculations of birds in orchards and vineyards of the Transcarpathian Region. showed that in the nesting period Sylvia nisoria and Turdus merula dominated in neglected orchards, Passer montanus-in the vineyards with fruit trees, Alauda arvensis, Sa- xicola rubetra and Oenanthe oenanthe-in the vineyards without woody plants. The total density of birds in the mentioned biotopes was 974, 914 and 200 individuals per 1 km2, respectively. In August the quality or birds in «pures vineyards was 215 individuals per 1 km2 (Coloeus monedula, Passer montanus and Saxicola rubetra are dominants) and in vineyards with fruit trees-1298.4 (Passer montanus and Fringilla coelebs are dominants).